An immune competent orthotopic model of endometrial cancer with metastasis. Issue 5 (May 2020) - Fedorko, Alyssa M.; Kim, Tae Hoon; Broaddus, Russell; Schmandt, Rosemarie; Chandramouli, Gadisetti V.R.; Kim, Hong Im; Jeong, Jae-Wook; Risinger, John I.
Abstract: Endometrial cancer is the most common gynecologic malignancy in the U.S. with metastatic disease remaining the major cause of patient death. Therapeutic strategies have remained essentially unchanged for decades. A significant barrier to progression in treatment modalities stems from a lack of clinically applicable in vivo models to accurately mimic endometrial cancer; specifically, ones that form distant metastases and maintain an intact immune system. To address this problem, we have established the first immune competent murine orthotopic tumor model for metastatic endometrial cancer by creating a green fluorescent protein labeled cell line from an endometrial cancer that developed in a Pgr cre/+ Pten f/f Kras G12D genetically engineered mouse. These cancer cells were grafted into the abraded uterine lumen of ovariectomized recipient mice treated with estrogen and subsequently developed local and metastatic endometrial tumors. We noted primary tumor formation in 59% mixed background and 86% of C57BL/6 animals at 4 weeks and distant lung metastases in 78% of mice after 2 months. This immunocompetent orthotopic tumor model closely resembles some human metastatic endometrial cancer, modeling both local metastasis and hematogenous spread to lung and has significant potential to advance the study of endometrial cancer and its metastasis. Abstract : Cancer research; Immunology; Genetics; Women's health; Reproductive system; Oncology; Alternative medicine; Laboratory medicine; Clinical research; Endometrial cancer; Metastasis; Orthotopic tumor model